Effect of pH-shifting treatment on structural and functional properties of whey protein isolate and its interaction with (−)-epigallocatechin-3-gallate. (15th February 2019) - Chen, Weijun; Wang, Wenjun; Ma, Xiaobin; Lv, Ruiling; Balaso Watharkar, Ritesh; Ding, Tian; Ye, Xingqian; Liu, Donghong
Highlights: pH-shifting treatment induced the structural changes of whey protein isolate (WPI). The structural changes resulted improved functional properties. Enhanced interaction of treated WPI and (-)-epigallocatechin-3-gallate (EGCG). Better protection of EGCG and its antioxidant activity in treated WPI. Abstract: Effect of pH-shifting on structural and functional properties of whey protein isolate and its interaction with (−)-epigallocatechin-3-gallate were investigated. Circular dichroism spectra showed that pH-shifting induced the decrease in α-helix content by 12.18% and β-sheet content by 3.24%, but β-turn and random coil content increased by 4.26% and 5.91%, respectively. Increase of fluorescence intensity and red-shift of maximum emission wavelength indicated the structural unfolding and exposure of tyrosine. The treatment also significantly increased the surface hydrophobicity, disulfide bonds content, solubility, emulsifying activity and emulsion stability of whey protein isolate at P < 0.05 level. Fluorescence quenching analysis revealed that treated whey protein isolate have a stronger binding affinity to (−)-epigallocatechin-3-gallate, resulting a better protection against the degradation of (−)-epigallocatechin-3-gallate and its antioxidant activity. This study confirmed that pH-shifting treatment can improve functional properties of whey protein isolate and its potential as a protective carrier for polyphones.